ANALYSIS OF THE C4.5 ALGORITHM IN PREDICTING FERTILIZER AND PESTICIDE SALES AT UD. MR ZEN AGRO - Sagala, Jijon Raphita; Hasugian, Penda Sudarto; Breukelen, Melisa Van; Nantheni, W.S.Usha (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
ABSTRACT Fertilizer and Pesticide sales prediction is a process for finding, assessing, and predicting fertilizer and pesticide sales for the future based on sales results in the past few months. The increasing demand from customers for Fertilizers and Pesticides means UD. Mr Zen Agro, which operates in supplying and selling necessities, needs to record sales transactions so that stock shortages and excess stock of goods do not occur. Using data mining techniques and applying the C4.5 Algorithm can help UD. Mr Zen Agro predicts sales of Fertilizers and Pesticides as a reference or guideline in making decision trees, which are able to predict sales data with a high level of accuracy by calculating the entropy value, information gain, split info, and gain ratio until the matter can no longer be calculated or is zero. An application system exists to predict sales of fertilizers and pesticides, which applies the C4.5 algorithm to UD. Mr Zen Agro, it can be seen how big the sales prediction results obtained can be implemented in a decision tree where from the decision tree, it can be seen which fertilizers and pesticides are in demand and which are not for sale. This system was built using the PHP programming language and MySQL as the database. Keywords: Data Mining, Sales Prediction, Fertilizer and Pesticide, Algorithm C4.5.   Keywords: Data Mining, Sales Prediction, Fertilizer and Pesticide, Algorithm C4.5.